Water quality monitoring via cloud application: Brief review - N. A., Abdul Muta’ali; Norazlianie, Sazali; S. A., Che Ghani; Walter, J. (IOP Publishing, 2021)
With the growing issue of water pollution and resources, the need for a remote water monitoring system has never been more crucial. The implementation of remote monitoring system has a growing interest in the current technology development. Evolution of wireless sensor networks, coding automation and control systems led to the introduction of Internet of Things. This paper aims to review a monitoring system via cloud application to make known of current available system. Cloud application system was studied extensively by various researcher, but research study focusing for water quality monitoring is still scarce. Two main objectives in the studies were designing low-cost system and ease of operation. Most of researchers designed their system using ZigBee, one of IoT system that is currently trending. Currently, cloud system was not widely applied in real industrial application due to lack of experimental evidence. Several enhancements that can be made were proposed.